2022
DOI: 10.1161/atvbaha.122.317514
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the GPR146 Gene Are Associated With a Favorable Cardiometabolic Risk Profile

Abstract: BACKGROUND: In mice, GPR146 (G-protein–coupled receptor 146) deficiency reduces plasma lipids and protects against atherosclerosis. Whether these findings translate to humans is unknown. METHODS: Common and rare genetic variants in the GPR146 gene locus were used as research instruments in the UK-Biobank. The Lifelines, and The Copenhagen-City Heart Study, and a cohort of individuals with familial hypobetalipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Rs1997243 and rs2362529, linked respectively to heightened and diminished expression of GPR146, can be considered independent genetic tools for investigating phenotypic associations related to the genetic ’activation’ or ’inhibition’ of GPR146. Employing this methodology across a wide range of phenotypes from the UK Biobank, we initially confirmed the initial observation that ’genetic inhibition’ of GPR146 (utilizing rs2362529 as an instrument) is significantly associated with plasma total cholesterol, LDL-C, and HDL-C, without impacting triglycerides or lipoprotein(a) plasma levels [14 ▪ ]. Additionally, utilizing data from the CARDIoGRAMplusC4D Consortium, we found that carriers of the rs2362529-C allele exhibit a slight but significant reduction in coronary artery disease compared to noncarriers.…”
Section: Genetic Evidences and Associated Phenotypesmentioning
confidence: 55%
See 2 more Smart Citations
“…Rs1997243 and rs2362529, linked respectively to heightened and diminished expression of GPR146, can be considered independent genetic tools for investigating phenotypic associations related to the genetic ’activation’ or ’inhibition’ of GPR146. Employing this methodology across a wide range of phenotypes from the UK Biobank, we initially confirmed the initial observation that ’genetic inhibition’ of GPR146 (utilizing rs2362529 as an instrument) is significantly associated with plasma total cholesterol, LDL-C, and HDL-C, without impacting triglycerides or lipoprotein(a) plasma levels [14 ▪ ]. Additionally, utilizing data from the CARDIoGRAMplusC4D Consortium, we found that carriers of the rs2362529-C allele exhibit a slight but significant reduction in coronary artery disease compared to noncarriers.…”
Section: Genetic Evidences and Associated Phenotypesmentioning
confidence: 55%
“…They further illustrated that rs1997243 exhibited enhanced promoter activity compared to its reference allele using reporter systems. In contrast to the findings for rs1997243, a recent study revealed that rs2362529 is associated with a reduction in GPR146 expression [14 ▪ ]. Notably, both cited variants are located in open-chromatin regions in the liver ( this review , data from [15]), providing additional support for their impact on the gene expression of GPR146 (Fig.…”
Section: Genetic Evidences and Associated Phenotypesmentioning
confidence: 68%
See 1 more Smart Citation
“…161 Further support comes from a recent study in humans showing that variation in the GPR146 gene locus is associated with reductions in both plasma levels of liver enzymes and cholesterol. 162 Taken together, there is considerable evidence for win-win opportunities. This review highlights, however, the need to increase our basic knowledge of VLDL biogenesis to identify and select the best targets for design of optimal strategies that will reduce ASCVD and steatotic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB and RANK ligand receptor activator expression in the joints of children with JIA may facilitate the survival of inflammatory cells in the joints [ 40 ]. Some studies have shown that GPR146 deficiency reduces lipids and prevents atherosclerosis [ 41 ], and the study by Clarke et al found that genetic susceptibility to juvenile idiopathic arthritis is associated with multiple cardiovascular risk factors [ 42 ], supporting the hypothesis of increased cardiovascular risk in juvenile idiopathic arthritis, suggesting that GPR146 may be associated with the development of JIA. TMEM158 was initially reported as a Ras-induced gene during aging and classified as an oncogenic or tumor suppressor depending on the tumor type [ 43 ].…”
Section: Discussionmentioning
confidence: 99%